"Clickable PEG" via anionic copolymerization of ethylene oxide and glycidyl propargyl ether. Issue 12 (10th March 2017) - Herzberger, Jana; Leibig, Daniel; Langhanki, Jens; Moers, Christian; Opatz, Till; Frey, Holger
Abstract : First one-step synthesis of poly(ethylene glycol) bearing multiple alkyne-groups along the polyether backbone and subsequent generation of PEG-glycopolymers by CuAAC. Abstract : A straight forward synthesis of poly(ethylene glycol) (PEG) with multiple alkyne groups distributed along the polymer chain is introduced. Direct access to clickable PEG is achieved by the monomer-activated anionic ring-opening copolymerization (AROP) of ethylene oxide (EO) with glycidyl propargyl ether (GPgE). Notably for successful polymerization no protection of the alkyne unit is required owing to the mild reaction conditions. Defined PEG- co -PGPgE and PGPgE (co)polymers with PDIs of 1.18–1.60 and molecular weights of M n = 3000–9500 g mol −1 were prepared. In situ 1 H NMR kinetic studies revealed remarkably disparate reactivity ratios of r EO = 14.8 and r GPgE = 0.076, representing a pronounced compositional drift with EO rich segments close to the initiator and GPgE units near the chain terminus, i.e. copolymers with a steep monomer gradient. Copper(i )-catalyzed azide–alkyne cycloaddition (CuAAC) with mannopyranosyl azide leads to PEG-based glycopolymers and highlights the potential of alkyne-functional PEGs as a universal scaffold for a range of biomedical applications.